Step-by-Step: a new WHO digital mental health intervention for depression - Carswell, Kenneth (Mhealth, 2018)
The World Health Organization is developing a range of interventions, including technology supported interventions, to help address the mental health treatment gap, particularly in low and middle-income countries. One of these, Step-by-Step, is a guided, technology supported, intervention for depression. It provides psychoeducation and training in behavioural activation through an illustrated narrative with additional therapeutic techniques such as stress management (slow breathing), identifying strengths, positive self-talk, increasing social support and relapse prevention. Step-by-Step has been designed so that it can be adapted for use in settings with different cultural contexts and resource availability and to be meaningful in communities affected by adversity. This paper describes the process of developing Step-by-Step and highlights particular design features aimed at increasing feasibility of implementation in a wide variety of settings.